The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000343374
|View full text |Cite
|
Sign up to set email alerts
|

Double Mutation at the Putative Protein Kinase C Phosphorylation Sites Thr151Plus Thr323in the Mouse LeukotrieneD4Receptor Eliminates Homologous Desensitization

Abstract: Background/Aims: Signalling via CysLT1 is involved in activation of volume sensitive K+ channels and homologous desensitization of the LTD4 receptor impairs regulatory volume decrease (RVD). The aim is to illustrate the effect of mutation of putative PKC consensus phosphorylation sites in the CysLT1R on desensitization and RVD. Methods: mCysLT1 contains 4 putative PKC consensus phosphorylation sites, and four mutants were created: Thr151Gly, Thr323Gly, Thr151Gly plus Thr323Gly, and Thr236… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It has been also demonstrated in several cell lines that inhibition of the 5-LO blocks volume restoration following osmotic cell swelling (30, 43) and the concomitant release of taurine (34,36). We have demonstrated that, in Ehrlich ascites tumor cells, leukotriene D 4 plays a key role in the activation of volume-sensitive transporters for K ϩ (15) and amino acids (31) and hence restoration of the cell volume following osmotic cell swelling (16,22,39). The 5-LO is a non-heme iron containing enzyme that is inactive when the iron is in the ferro state (Fe 2ϩ ) and active when the iron is in its oxidized ferri state (Fe 3ϩ ).…”
mentioning
confidence: 83%
“…It has been also demonstrated in several cell lines that inhibition of the 5-LO blocks volume restoration following osmotic cell swelling (30, 43) and the concomitant release of taurine (34,36). We have demonstrated that, in Ehrlich ascites tumor cells, leukotriene D 4 plays a key role in the activation of volume-sensitive transporters for K ϩ (15) and amino acids (31) and hence restoration of the cell volume following osmotic cell swelling (16,22,39). The 5-LO is a non-heme iron containing enzyme that is inactive when the iron is in the ferro state (Fe 2ϩ ) and active when the iron is in its oxidized ferri state (Fe 3ϩ ).…”
mentioning
confidence: 83%
“…Furthermore, PKC‐mediated phosphorylation/desensitization of the mCysLT1 receptor have recently been assigned a role in abrogation of the RVD response (Jorgensen et al . ).…”
Section: Taurine Transportersmentioning
confidence: 97%
“…The phosphatase required for PTEN activation has not been identified, and it is also unknown whether PTEN activity is affected by osmotic cell swelling. Abrogation of the volume-regulatory process in EATC involves PKC-mediated phosphorylation and desensitization of the CysLT1 receptor (18). VSOAC has not been cloned although date indicates that it is different from volume-sensitive Cl Ϫ channels (27,29) and Ca 2ϩ -sensitive Cl Ϫ channels (19).…”
mentioning
confidence: 99%